2020
DOI: 10.1371/journal.pone.0244073
|View full text |Cite
|
Sign up to set email alerts
|

A phenomenological study on the lived experiences of families of ICU patients, Addis Ababa, Ethiopia

Abstract: Background Family-centered care of ICU patients is increasingly recommended as it is believed to have effect on family members’ psychosocial status and patient outcomes. Defining the nature and extent of families’ involvement in a given health care environment for different stakeholders is a challenge. Understanding the lived experiences of families of ICU patients would help strategize on how to better engage family members for improved ICU care processes and outcomes. Objectives The aim of this study is to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
1
2
0
2
Order By: Relevance
“…Similarly, this study found that limiting parent-neonate relationships causes di culties for parents. This is supported by other studies that revealed that limited parent-child interaction, restricted visiting hours, or perceived restrictions on parental involvement are the main sources of parental psychological tension and fear in the NICU(18, 19,33,34,40).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Similarly, this study found that limiting parent-neonate relationships causes di culties for parents. This is supported by other studies that revealed that limited parent-child interaction, restricted visiting hours, or perceived restrictions on parental involvement are the main sources of parental psychological tension and fear in the NICU(18, 19,33,34,40).…”
Section: Discussionsupporting
confidence: 75%
“…Besides, the separation of the sick baby creates another terror (29), it may be a source of emotional and cognitive burden when communications are inappropriate (17,(30)(31)(32). Studies reveal that limited parent-child interaction, restricted visiting hours, or perceived restrictions on parental involvement are the main sources of psychological stress in the NICU ward of a hospital (18, 19,33,34).…”
Section: Introductionmentioning
confidence: 99%
“…Inclusion criteria for participants included the family members who were in close relationship and living with or were the main caregivers the patients with suspected or confirmed COVID-19 [confirmed by a specialist through Chest CT scan or positive PCR and receiving standard medical interventions as well as patients who have been admitted to the ICU for a maximum of 24 hours (The first 24 hours in critically ill patients is the most crucial time for the family members, because they experience a sudden stressful event (Kehali et al, 2020). )] with moderate to severe pulmonary involvement with O 2 saturation of 93 and below in ABGs results, the possibility of communicating via the web, the age range of 18 to 65 years, and no current or previous employment as a member of the health care team.…”
Section: Methodsmentioning
confidence: 99%
“…Además, se ve aumentada las creencias religiosas al encomendar su salud en manos de Dios y el nivel de ansiedad se ve disminuido cuando el personal de enfermería da una buena atención. Por otra parte, (Kehali et al, 2020) encontraron que en la familia existe una carga financiera por los altos costos de la UCI en hospitales privados lo que generan gran tensión psicológica, ya que los familiares generalmente dejan de trabajar de manera regular y pueden perder su empleo, lo que abruma a la familia en la toma de decisiones e interrumpe las rutinas del hogar. Se menciona también que el apoyo y la atención por parte del personal de salud solo va dirigida a satisfacer las necesidades del paciente, sin considerar al familiar lo que provoca un impacto en la calidad de atención.…”
Section: Metodologíaunclassified
“…Estos factores incluyen en las emociones, la religiosidad, aspectos económicos, la comunicación, el apoyo emocional y la relación que mantiene con el personal de salud. Estos hallazgos concuerdan con los estudios realizados por (Santiago & Vargas, 2015), (Kehali et al, 2020) y (Corrêa et al, 2021).…”
Section: Metodologíaunclassified